Metabolomics profiles of the liquid co-culture of Sanghuangporus vaninii and Pleurotus sapidus - Lu, Yuantian; Liu, Di (Frontiers in Sustainable Food Systems, 2024)
Introduction Fungal secondary metabolites (SMs) have broad application prospects in the food and medicine industries. Co-culturing strategies that simulate natural symbiotic relationships among microorganisms are used to discover and enhance the production of new SMs. We aimed to use the abundant resources of large edible and medicinal fungi to enhance the yield of desired metabolites through co-culture and potentially produce metabolites that cannot be generated in pure cultures. Methods We assessed the biomass and intracellular polysaccharide (IPS) content of liquid co-cultures of Sanghuangporus vaninii and Pleurotus sapidus. Subsequently, the effect of the liquid co-culture on fungal intracellular metabolites was studied using UPLC-QTOF. Results Co-culturing of S. vaninii with P. sapidus resulted in significantly increased biomass and IPS content; however, P. sapidus had a significant inhibitory effect on the growth of S. vaninii. Metabolomic data further indicated that amino acid, nucleotide, and glycerophospholipid metabolisms were the primary metabolic pathways affected by symbiosis. Discussion This study provides insights into fungal interactions and cellular metabolic mechanisms, contributing to the understanding and enhancement of the fungal fermentation potential.